Performance of Hybrid Aeration-Pre-sedimentation Process in Microplastic Removal from Raw Water - Arlini Dyah Radityaningrum; Rahmatdani Rizqi’ain; Ro’du Dhuha Afrianisa; Catur Bagus Priyono (Poltekkes Kemenkes Surabaya, 2024)
Plastic materials can degrade into small particles known as microplastics (MP) and nanoplastics (NP). The presence of MP has been detected in treated drinking water. Aeration and pre-sedimentation are preliminary treatment processes in Water Treatment Plants (WTP), which can potentially remove MP pollutants. This study aims to (1) determine the abundance and characteristics of MP in raw water samples and effluents from the hybrid aeration-pre-sedimentation process; (2) determine the efficiency of MP removal in the hybrid aeration-pre-sedimentation process. This study was conducted on a laboratory scale. Raw water samples (2.5 L) were collected from Kali Jagir Surabaya. The test reactor consisted of a cascade aerator (5 and 7 steps) and pre-sedimentation, operated in batch mode. Identification of MP abundance and characteristics (shape, size, color, polymer type) was conducted on samples before treatment (aeration influent) and after treatment (pre-sedimentation effluent). Sampling was performed in triplicates at 2 and 4-hour detention times. Test samples were extracted through oxidation with H2O2 and membrane filtration using PTFE (pore size 0.22 µm; diameter 47 mm). MP particles were observed using a Dino-Lite digital microscope. Polymer type was determined by FTIR testing. The results showed that the average abundance of MP in the influent sample was 8.5 particles/L, while in the effluent of the hybrid cascade aerator-pre-sedimentation reactors (5 and 7 steps), it was 1 and 6.5 particles/L, respectively. MP particles’ dominant size and shape were 101-350 µm and fibers. Transparent and white colors predominated the MP particles. The polymer type of MP found in raw water samples was polyethylene (PE). The highest MP removal efficiency in the hybrid aeration-pre-sedimentation process with 2 and 4-hour detention times were 88% and 24%, respectively.